Long-Term in Vitro Corrosion of Biodegradable WE43 Magnesium Alloy in DMEM - Julia Nachtsheim; Jaka Burja; Songyun Ma; Bernd Markert (Metals, 2022)
The biodegradable WE43 magnesium alloy is an attractive biomedical material for orthopaedic implants due to its relatively high strength and corrosion resistance. Understanding the long-term corrosion behaviour in the human body plays a crucial role in the biomedical development and application of WE43 alloy for orthopaedic implants. In this work, the corrosion of an extruded WE43 magnesium alloy was investigated in a physiological environment using Dulbecco’s Modified Eagle Medium’s (DMEM) over a period of up to 10 weeks. To assess the in vitro corrosion process, we analysed the corrosion pits of the specimens’ cross sections and the composition of the corrosion layer by scanning electron microscopy. The experimental results indicated that the long-term corrosion process of WE43 magnesium alloy consists of three stages: (1) The rapid corrosion stage within the first 7 days, (2) the steady corrosion stage between 7 and 28 days, (3) the accelerated corrosion stage between 28 and 70 days. The microchemical analysis revealed a heterogeneous three-layer corrosion product with varying thicknesses of 10 to 130 µm on the surfaces of the samples for all corrosion times. It is composed of an inner layer of Mg-O, an intermediate layer of Mg-O-Ca-P, and an outer layer of Mg-O-Ca-P-C. The corrosion layers have many microcracks that allow limited contact between the liquid medium and the surface of the alloy. In addition, microgalvanic corrosion was observed to cause corrosion pits between the intermetallic rare earth element-rich phases and the Mg matrix.